The Influence of Internal Control System, Cash Sales On Regional Asset Management Receipts - Otniel Safkaur (Yayasan Ilomata, 2021)
The internal control system is a process, which is influenced by human resources and information technology systems, which are designed to help an organization achieve a goal. The internal control system is a way to direct, supervise, and measure the resources of a regional financial management apparatus. The purpose of the internal control system is to achieve goals and guarantee or provide accurate financial reports and ensure compliance with laws and regulations. The internal control system, consisting of policies and procedures used in company operations to provide reliable financial information and ensure compliance with applicable laws and regulations. At the regional financial management apparatus level, the objectives of internal control are related to the reliability of financial reports, timely feedback on the achievement of operational and strategic objectives, and compliance with laws and regulations on cash receipts. At a specific transaction level, internal control refers to actions taken to achieve an objective to ensure payment, receipt of cash from third parties for a service that is performed). Internal control system procedures reduce process variations and cash receipt transactions and provide more accurate results. The population in this study were 44 SKPDs in the Skouw Mabo, Skouw, Yambe, Skouw Sae, and Mosso areas, Muara Tami District, Jayapura City. These four areas are the border areas of the Republic of Indonesia and Papua New Guinea. The sample collection method is purposive sampling by taking samples from the regional financial management apparatus. The data analysis technique used in this study was SEM PLS. The results of this study indicate that the internal control system, cash sales affect cash receipts.